Analysis of the Organizational Structure of the Health Service of the Principality of Asturias (SESPA). Past, Present and Challenges for the Future - Pimenta, Clayson Cosme Da Costa; Prieto, Daniel Zarzuelo; Primo, Luis Rodríguez; Piñera, Laura Rodríguez (Scholars Journal of Arts, Humanities and Social Sciences, 2024)
This article deals with the reorganization of the health map in the Principality of Asturias, highlighting the reduction of the current eight areas to three as the central axis of the proposal. The unification seeks to optimize resources, improve operational efficiency and offer more integrated health services adapted to the changing needs of the population. Structural changes are detailed, including the possible creation of new departments and sub-directorates, as well as the concentration of healthcare services in the university hospitals, which could generate additional displacements for users. The concerns of healthcare professionals and unions are analyzed, especially in terms of forced mobility, which could affect job satisfaction and quality of care. Concerns about working conditions are also highlighted, as well as the possible effects on resource management and bureaucracy. The Regional Ministry of Health highlights the expected benefits, such as improved management of human and technological resources and the attraction of talent, as well as assuring that there will be no hospital closures, and that the reorganization will not negatively affect the quality of care or working conditions. Finally, the paper concludes that, although some objectives have been met, others require further analysis and could be the subject of future research.